Eksplorasi Adaptasi Ibu dalam Upaya Pengentasan Stunting - Indra Dewi; Susi Sastika Sumi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore the adaptation experiences of parents to eradicate stunting in the Gowa Regency area, especially in Pallantikang Village, Gowa Regency. The method used is qualitative research using a phenomenological design. The results of this study indicate that there are three themes related to parents' adaptation experiences to eradicate stunting in the Gowa Regency Region, 1) mothers provide food based on the age of the toddler; 2) mother's parenting style based on the toddler's needs; 3) the mother maintains the health of the toddler. In conclusion, the ability of mothers to adapt to changes that occur in toddlers is very influential in efforts to overcome stunting. Parents' adaptation in efforts to eradicate stunting has a huge role and influence on the growth and development of toddlers. Keywords: Mother's Adaptation, Exploration, Stunting Alleviation